PENGARUH IPM, UMP DAN INFLASI TERHADAP PENYERAPAN TENAGA KERJA (Era Bonus Demografi Pulau Jawa Tahun 2012-2021) - Kalsum, Ika Afida; Faisal Fadli (Journal of Development Economic and Social Studies, 2024)
Populations growth, which is only concentrated on the island of java, has result in an abundance of manpower on the island, but employment is still a problem because labor absorption is not optimal, as evidenced by the high open unemployment rate. On the other hand, the phenomenon of the dividen demographic is still going on, and now the productive age group must be used optimally for the success of economic development later in 2030. The use of the dividen demographic is one of them by increasing employment to reduce unemployment. This study aims to determine the effect of HDI, UMP, and Inflation on employment in java in 2012-2021. This research method uses multiple linear regression with panel data, but the method contains outliers, so it uses robust regression. The results of this study partially indicate that the HDI, as indicated by education, has a negative and significant effect on employment, whereas health and GRDP per capita have a positive effect on employment. Then inflation has a negative and significant effect, while UMP has a negative and insignificant effect. Then it simultaneously shows how education, health, GDRP/capita, inflation, and UPM affect employment absorption.